Răspuns :
0,25a²-2ab+4b²= (a/2-2b)²
se aplica formula x²-2xy+y²=(x-y)²
in cazul nostru
x²=0,25a²=25a²/100 =a²/4 ⇒x=√a²/4 ⇒x=a/2
y²=4b² ⇒ y=√4b²⇒y=2b
-2xy=-2×a/2×2b=-2ab
se aplica formula x²-2xy+y²=(x-y)²
in cazul nostru
x²=0,25a²=25a²/100 =a²/4 ⇒x=√a²/4 ⇒x=a/2
y²=4b² ⇒ y=√4b²⇒y=2b
-2xy=-2×a/2×2b=-2ab
[tex] 0,25a^{2} - 2ab+ 4b^{2} = \frac{25}{100} a^{2} - 2ab+ 4b^{2} = \frac{1}{4} a^{2}-2ab+ 4b^{2} = ( \frac{1}{2} a-2b )^{2} [/tex]
Conform formulei : [tex] a^{2} -2ab+ b^{2} =(a-b )^{2} [/tex]
Conform formulei : [tex] a^{2} -2ab+ b^{2} =(a-b )^{2} [/tex]